Servqual: Service quality assessment from the students expectations and perceptions in comparison with the students academic performance at the Hulu Selangor district secondary schools / Shamsida Mohd Nor and Osman Jusoh - Mohd Nor, Shamsida; Jusoh, Osman (2004)
SERVQUAL stands for Servis Quality which can be quantified from the difference or the gap between perceptions and expectations of customers. Expectations are the reference point customers have coming into service experience; perceptions reflect the service as actually received by the customers. The purpose of this study was to gather information about the expectations and perceptions of students who are considered as customers, regarding their schools service quality. The higher mean of SERVQUAL indicates the higher quality of the organization being assessed. Service quality offered by the school has been compared to the academic performance based on the PMR results of the year 2003 to see if there is a significance correlation between the two. The statements in the SERVQUAL instrument were reviewed and adapted from business to educational terms and formulated into a 22 statement of Part A of the questionnaire. In Part B, the relative importance of each dimension was identified and demographic section was in Part C. Three hundred and thirty six respondents from twelve schools in the Hulu Selangor district have been selected to answer the questions. The 22- statement SERVQUAL instrument, measuring the five service dimensions of tangibles, reliability, responsiveness, assurance, and empathy, was administered to those students during a two-week data collection period. In the data analysis, the Expectation-Service Gap Grid was used to identify service shortfalls under these five dimensions and statistical technique of correlation has been used to identify the relationship between service quality and academic performance. This paper ends with conclusion and recommendation